Autonomy support beyond the language learning classroom : a self-determination theory perspective - Mynard, Jo; Shelton-Strong, Scott J., 1966- (Multilingual Matters, 2022)
"Through the application of self-determination theory (SDT) to research and practice, this book deepens our understanding of how autonomous language learning can be supported and understood outside of the classroom. The chapters deal with learning environments and open spaces, communities and relationships, and advising and self-access"-- Provided by publisher
Keywords: Second language acquisition -- Psychological aspects.; Language and languages -- Study and teaching -- Psychological aspects.; Autonomy (Psychology); Motivation in education.; Informal language learning.; Non-formal education.; Second language acquisition.; Langue seconde -- Acquisition -- Aspect psychologique.; Langue seconde -- Acquisition.; Motivation en éducation.; Apprentissage informel des langues.; Éducation non formelle.; PSYCHOLOGY -- General.; Informal language learning; Language and languages -- Study and teaching -- Psychological aspects; Motivation in education; Non-formal education; Second language acquisition -- Psychological aspects; PSYCHOLOGY / General; Essay; essays.; Essays; Essays.; Essais.